Gas hydrate dissociation off Svalbard induced by isostatic rebound rather than global warming - Wallmann, Klaus; Riedel, M.; Hong, Wei-Li; Patton, Henry; Hubbard, Alun Lloyd; Pape, T.; Hsu, C.W.; Schmidt, C.; Johnson, Joel E.; Torres, M.E.; Andreassen, Karin; Berndt, C.; et al. (Nature Communications, 2018)
Source at: http://doi.org/10.1038/s41467-017-02550-9 Methane seepage from the upper continental slopes of Western Svalbard has previously been attributed to gas hydrate dissociation induced by anthropogenic warming of ambient bottom waters. Here we show that sediment cores drilled off Prins Karls Foreland contain freshwater from dissociating hydrates. However, our modeling indicates that the observed pore water freshening began around 8 ka BP when the rate of isostatic uplift outpaced eustatic sea-level rise. The resultant local shallowing and lowering of hydrostatic pressure forced gas hydrate dissociation and dissolved chloride depletions consistent with our geochemical analysis. Hence, we propose that hydrate dissociation was triggered by postglacial isostatic rebound rather than anthropogenic warming. Furthermore, we show that methane fluxes from dissociating hydrates were considerably smaller than present methane seepage rates implying that gas hydrates were not a major source of methane to the oceans, but rather acted as a dynamic seal, regulating methane release from deep geological reservoirs.